2020
DOI: 10.1177/1934578x20953954
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activities of Coumarin Compounds in Licorice: A Review

Abstract: Licorice is a traditional medicine commonly used in China and many other countries. Over the last 50 years, the structure and pharmacological effects of coumarin compounds in licorice have been investigated. However, a comprehensive review of the literature summarizing current trends is currently lacking. Thus, the aim of the present review is to provide an up-to-date summary of the scientific literature regarding the pharmacological effects of coumarin compounds in licorice, thereby laying the foundation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 106 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…Coumarins are among the main active ingredients of medicinal plants. They exhibit various biological activities, such as anti‐inflammatory, antibacterial, antiviral, anticoagulant, immunosuppressive, and antitumor activities 17 . They are divided into four major groups according to their substituents: simple coumarins, furan coumarins, pyranocoumarins, and other coumarins.…”
Section: Resultsmentioning
confidence: 99%
“…Coumarins are among the main active ingredients of medicinal plants. They exhibit various biological activities, such as anti‐inflammatory, antibacterial, antiviral, anticoagulant, immunosuppressive, and antitumor activities 17 . They are divided into four major groups according to their substituents: simple coumarins, furan coumarins, pyranocoumarins, and other coumarins.…”
Section: Resultsmentioning
confidence: 99%
“…96,97 Similar to the chalcone derivatives, coumarin compounds in licorice have significant radical scavenging activity. 98,99 Moreover, saponins and polysaccharides isolated from licorice have been reported to exert antioxidant activities. [100][101][102] Consequently, it seems that the triterpenes, chalcones, coumarins, flavonoids, isoflavones and methylated isoflavones have significant antioxidant activity inhibiting the processes of carcinogenesis, and these contents of licorice have great potential as novel anticancer agents.…”
Section: Phase II Pathwaysmentioning
confidence: 99%
“…The role of licorice in Japan also needs to be highlighted as they have been using it to treat chronic hepatitis [68]. The plant also has anticancer, hepatoprotective, antispasmodic, neuroprotective, antioxidant, and estrogenic properties and is very useful in reducing hepatocellular damage in chronic hepatitis B and C patients [69]. For many years, it has had the reputation of being a memory booster [70] and an antidepressant [71] and can reduce blood cholesterol levels [72,73] and acts as a promising drug for treating liver and renal complications [74][75][76].…”
Section: Licorice (Glycyrrhiza Glabra)mentioning
confidence: 99%
“…For many years, it has had the reputation of being a memory booster [70] and an antidepressant [71] and can reduce blood cholesterol levels [72,73] and acts as a promising drug for treating liver and renal complications [74][75][76]. It is also found that the plant can reduce polydipsia and frequent urination in diabetic patients [69]. In some places, the root is used to prepare tea, and the dried root is used as a tooth cleanser [77].…”
Section: Licorice (Glycyrrhiza Glabra)mentioning
confidence: 99%